Application of proteomics to determine the mechanism of ozone on sweet cherries (Prunus avium L.) by time-series analysis - Zhao, Yuehan; Hou, Zhaohua; Zhang, Na; Ji, Haipeng; Dong, Chenghu; Yu, Jinze; Chen, Xueling; Chen, Cunkun; Guo, Honglian (Frontiers in Plant Science, 2023)
This research investigated the mechanism of ozone treatment on sweet cherry (Prunus avium L.) by Lable-free quantification proteomics and physiological traits. The results showed that 4557 master proteins were identified in all the samples, and 3149 proteins were common to all groups. Mfuzz analyses revealed 3149 candidate proteins. KEGG annotation and enrichment analysis showed proteins related to carbohydrate and energy metabolism, protein, amino acids, and nucleotide sugar biosynthesis and degradation, and fruit parameters were characterized and quantified. The conclusions were supported by the fact that the qRT-PCR results agreed with the proteomics results. For the first time, this study reveals the mechanism of cherry in response to ozone treatment at a proteome level.